Parents’ Sharenting Behaviours: A Systematic Review of Motivations, Attitudes, Perceptions, and Impression Management Perspectives - Saied, Motevalli; Rogayah, A. Razak; Richard Peter, Bailey; Amalia, Madihie; Katayoun, Mehdinezhadnouri; Yifei, Pan (F1000 Research Ltd,\, 2025)
Introduction Sharenting involves parents sharing photos, videos, or other information about their children on their social media profiles via online platforms. Research indicated the rising prevalence of parental sharenting behaviour among various countries.